Ten years of clinical experience with biosimilar human growth hormone: a review of safety data - Borrás Pérez MV; Kriström B; Romer T; Walczak M; Höbel N; Zabransky M (Dove Medical Press, 2017)
Maria Victoria Borrás Pérez,1 Berit Kriström,2 Tomasz Romer,3 Mieczyslaw Walczak,4 Nadja Höbel,5 Markus Zabransky5 1Hospital General de Granollers, Granollers, Barcelona, Spain; 2Department of Clinical Sciences, Pediatrics, Umeå University, Umeå, Sweden; 3Department of Endocrinology, Children’s Health Research Institute, Warsaw, 4Department of Paediatric Endocrinology and Diabetology, Pomeranian Medical University, Szczecin, Poland; 5Sandoz Biopharmaceuticals, Hexal AG, Holzkirchen, Germany Abstract: Safety concerns for recombinant human growth hormone (rhGH) treatments include impact on cancer risk, impact on glucose homeostasis, and the formation of antibodies to endogenous/exogenous GH. Omnitrope® (biosimilar rhGH) was approved by the European Medicines Agency in 2006, with approval granted on the basis of comparable quality, safety, and efficacy to the reference medicine (Genotropin®). Additional concerns that may exist in relation to biosimilar rhGH include safety in indications granted on the basis of extrapolation and the impact of changing to biosimilar rhGH from other rhGH treatments. A substantial data set is available to fully understand the safety profile of biosimilar rhGH, which includes data from its clinical development studies and 10 years of post-approval experience. As of June 2016, 106,941,419 patient days (292,790 patient-years) experience has been gathered for biosimilar rhGH. Based on the available data, there have been no unexpected or unique adverse events related to biosimilar rhGH treatment. There is no increased risk of cancer, adverse glucose homeostasis, or immunogenic response with biosimilar rhGH compared with the reference medicine and other rhGH products. The immunogenicity of biosimilar rhGH is also similar to that of the reference and other rhGH products. Physicians should be reassured that rhGH products have a good safety record when used for approved indications and at recommended doses, and that the safety profile of biosimilar rhGH is in keeping with that of other rhGH products. Keywords: recombinant human growth hormone, Omnitrope®, biosimilar